Образ козацької України у творах Т.Шевченка - Щербак, В.О. (Український історичний журнал, 2014)
Висвітлюється образ козацької України в поетичній спадщині Тараса Шевченка. Проаналізовано історичні джерела, які він використовував, та реалії сучасної поету епохи. Увага акцентується на творах, що відображали найбільш яскраві події та явища козацької доби. The article highlights the image of Cossack Ukraine in the poetical heritage of T.Shevchenko. Sources, which he used, and historical realities of poet’s era were analyzed. The attention is paid to the works where the most vivid events and phenomena of Cossack era are depicted.